Embroidering care and reciprocity: contributions to food sovereignty by feminist peasant women from the mountains of Veracruz, Mexico - Pontes, Thelma Mendes; Merçon, Juliana; López Binnqüist, Citlalli; Cerdán, Carlos Roberto; Illescas Palma, Gisela; García Moreno, Denisse; Severiano Hernández, Mónica; Morales, Helda (Frontiers in Sustainable Food Systems, 2024)
Different authors from academia and social movements point to agroecology as a path to food sovereignty and as a way out of multiple social-ecological crises. Peasant feminism (feminismo campesino) informs the daily practice of women, and has contributed to broaden the meanings of food sovereignty as a political framework. Vinculación y Desarrollo Agroecológico en Café (VIDA) is a Mexican coffee growers’ organization that is centrally guided by principles of agroecology, food sovereignty, and peasant feminism. A transdisciplinary study held with VIDA members shows how food sovereignty is based on more dimensions than the official ones. In this paper, we use the Mexican art of embroidery as an integrating metaphor to analyze how female coffee growers’ practices around integral health, food gathering, and bartering contribute to food sovereignty. Our intention is also to analyze how these activities expand from the family unit to the territory, as well as from human to more than human beings. Based on their agroecological knowledge and practice, VIDA’s feminist peasant women invite us to consider agroecology and food sovereignty as key dimensions of Earth stewardship.